K interpretacii slučaev upotreblenija -l- formy bez svjazki - Skačedubova, Marija Vadimovna (Slavistična revija, 2017)
The article analyzes instances of verbal l-forms used without auxiliary in Old Russian Hypatian Chronicle (13th-15th c.). Special emphasis is on the contexts where l-forms do not convey the meaning of the perfect tense. One part consists of contexts that are typical for participle predications. The other part consists of examples where the l-forms appear in typical participle contexts of the vstav (i) reče type. All examples where l-forms do not have the meaning of the perfect tense can be attributed either to the first or to the second group. Taking this into account, as well as the material from the dialects and other Slavic languages that include, to varying extent, adjectives going back to l-participles, it seems reasonable to assume that l-forms could function not only as a part of the compound verbal predicate, but also as a past participle -š-/-vš-.
Keywords: 14. st.; deležnik; Ipatjevski letopis; pretekli čas; Russian; ruščina; stara ruščina